Association of Diffusion Weighted Magnetic Resonance Imaging Profile and Apparent Diffusion Coefficient Value with Brain Tumor’s Histopathology - Hartati Rusmi Tri Wilujeng1, Anggraini Dwi Sensusiati2, M. Yamin Sunaryo Suwandi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Accuracy of preoperative brain tumor’s histopathologic differentiation is very important to determine preoperative staging, intraoperative management and postoperative therapy. Diffusion weighted magnetic resonance imaging is an advanced technique developed as an important method for brain tumor assessment. Objectives: This study aimed to investigate correlation between diffusion weighted imaging (DWI) profile and apparent diffusion coefficient (ADC) value with brain tumor’s histopathology. Methods: This study examined 86 subjects with brain tumors using magnetic resonance imaging and histopathology examination at Dr. Soetomo Teaching Hospital and evaluated DWI profile and ADC maps. The spherical ROI on ADC maps was placed on the solid part of the tumor to measure ADC value. Spearman’s correlation test was conducted to determine correlation between DWI profile and ADC values with histopathological grading and types of brain tumor. Results: There was a significant correlation between DWI profile and ADC values (p = 0.000), as well as DWI and ADC values with histopathological grading and types of brain tumor (p = 0.000). There was an inverse corelation between ADC value and histopathological grading. The higher the ADC value, the lower the brain tumor grade, while lower ADC value resulted in high tumor grade. The average ADC value of grade-1 meningiomas was 1.061±0.257 x 10-3 mm2/sec, pilocytic astrocytoma was 1.301±0.107 x 10-3 mm2/ sec, glioblastoma multiforme was 0.831±0.080 x 10-3 mm2/sec, and medulloblastomas was 0.600±0.078 x 10-3 mm2/sec. Conclusion: Evaluation on DWI profile and ADC value could provide additional information on conventional magnetic resonance imaging examination to determine histopathological grading and types of both intra and extra-axial brain tumors.